Religioznyj i informacionnyj radikalizm v molodežnoj srede - Baitenova, N. Zh (Chabaršy. Dintanu serijasy, 2019)
The role of the social phenomenon of religious extremism and terrorism in the modern world is enormous, especially among young people. However, in almost every state there is a different approach to understanding the essence of religious extremism and terrorism, the reasons for their occurrence, the assessment of their manifestations; the same political phenomena are assessed as the struggle of nations for self-determination, as a positive development process, and as religious extremism and terrorism, destructive, criminal activity, which is essentially outside the law. It should be noted that the main reasons for the formation of extremist attitudes and ideas among the youth have persisted since the early 1990s. In recent years, the situation has become seriously complicated due to the penetration of international extremist movements and groups into the Internet space. In recent years, both in Kazakhstan and abroad, several significant events have occurred, which have shown that young people in various countries are vulnerable to extremist influences. In recent years, youth religious extremism has acquired a global character, by means of modern information and communication technologies spreading throughout the world, including in Kazakhstan. The situation is complicated by serious problems associated with a weak empirical study of informational religious radicalism, its causes, the scale of distribution, the forms of manifestation and the degree of influence on the consciousness of young people.